Magyar nevek beillesztése a finn ragozási rendszerbe - Koivunen, Tomi (Collegium Fenno-Ugricum, 2025)
Finnish nouns are divided into inflectional groups. The exact number of
groups depends on the source: for example, in Suomen kielen perussanakirja
(Basic dictionary of the Finnish language, 1990–1994) nominals have 49 inflection
types, but in textbooks the total number of inflection types is usually
not defined. Conjugation type refers to a group of words that are inflected in
the same way, of which the productive ones also provide a model for the inflection
of new words. Differentiating the types of inflections is influenced
by the stem type of the word, the stem variation occurring in the inflectional
forms, and suffix variants.
Loan nouns must be placed in one of the inflectional groups in order to
be inflected. A common way to adapt loanwords is the so-called epenthetic i,
which is added to the end of the source language word. The same i often also
occurs in the inflectional stem of consonant-ending loanwords and, for example,
proper nouns. However, the rule is not without exceptions, and in addition,
many proper names of foreign origin cause orthographic challenges.
The goal of my research is to find out how Hungarian proper names and
possible other loanwords are inflected in written Finnish. I use online texts as
material sources and especially the online version of Iso suomen kielioppi (Big
grammar of Finnish, VISK, 2008) and Kielitoimisto’s (Language office) instruction
bank as sources of theory.
Hungaro-Baltica 2. A Baltikumtól a Kárpát-medencéig